A simple synthetic entryway into palladium cross-coupling catalysis. Issue 57 (14th June 2017) - Zinser, Caroline M.; Nahra, Fady; Brill, Marcel; Meadows, Rebecca E.; Cordes, David B.; Slawin, Alexandra M. Z.; Nolan, Steven P.; Cazin, Catherine S. J.
Abstract : The simple synthesis of a family of palladates containing an imidazolium counterion is presented. These "ate" complexes can be easily converted into well-defined palladium–N-heterocyclic carbene (NHC) complexes. Abstract : The simple synthesis of a family of palladates containing an imidazolium counterion is presented. These "ate" complexes can be easily converted into well-defined palladium–N-heterocyclic carbene (NHC) complexes. The synthetic protocols leading to the "ate" and to the Pd–NHC neutral complexes have been exemplified with various NHC ligands. The palladates prove efficient pre-catalysts enabling Suzuki–Miyaura and Mizoroki–Heck reactions.